THU0511 Factors Associated with Preclinical Atherosclerotic Changes in Carotid Artery in Men with Gout. (15th July 2016) - Tag, H.; Kim, G.; Park, E.; Koo, D.; Lee, J.; Kim, S.
Abstract : Background: Although a number of studies have reported that hyperuricemia and gout are independent risk factors for the development of cardiovascular disease (CVD), little is known about the relationship between hyperuricemia or gout and arterial stiffness. Objectives: This study sought to compare carotid arterial stiffness in gout patients and healthy controls, and evaluate the predictive factors for arterial stiffness in male patients with gout using carotid ultrasonography. Methods: In this cross-sectional study, 69 male gout patients and 64 male healthy controls without any known CVD were prospectively analyzed. Carotid artery stiffness index β (β-index) and the intima-media thickness (IMT) were measured as surrogate markers of preclinical atherosclerosis. We also measured serum uric acid, high sensitivity C-reactive protein (hsCRP), erythrocyte sedimentation rate (ESR), lipid profiles, and renal function. Adjusted comparison of the β-index and cIMT in both groups and their associations with clinical parameters were investigated. Results: The gout group showed higher ESR, Cr, prevalence of HT and DM than the control group (p<0.05). However, HDL was higher in the control group (p<0.05). β-index and cIMT were higher in the gout group, but only β-index showed a statistically significant difference (11.12 ± 5.19 vs 8.68 ± 3.67, p=0.002). Multiple regression analyses showed that duration of gout was significantly associated with increased β-index and cIMT in the gout group (Table 1 ). Conclusions: Patients with gout had increased carotid arterial stiffness, which was significantly related to gout duration rather than serum uric acid level or status of inflammation. References: Richette P, Perez-Ruiz F, Doherty M, Jansen TL, Nuki G, Pascual E, Punzi L, So AK, Bardin T. (2014) Improving cardiovascular and renal outcomes in gout: what should we target? Nat Rev Rheumatol. 10(11):654–61. Perez-Ruiz F, Becker MA. (2015) Inflammation: a possible mechanism for a causative role of hyperuricemia/gout in cardiovascular disease. Curr Med Res Opin. 31 Suppl 2:9–14. Disclosure of Interest: None declared